General and Scalable Approach to A2B‐ and A2BC‐Type Porphyrin Phosphonate Diesters. Issue 28 (6th October 2016) - Enakieva, Yulia Yu.; Michalak, Julien; Abdulaeva, Inna A.; Volostnykh, Marina V.; Stern, Christine; Guilard, Roger; Bessmertnykh‐Lemeune, Alla G.; Gorbunova, Yulia G.; Tsivadze, Aslan Yu.; Kadish, Karl M.
Abstract : A two‐step reaction sequence for accessing meso ‐(dialkoxyphosphoryl)porphyrins from readily available trans ‐A2 ‐type porphyrins was developed. This approach involves bromination and subsequent palladium‐catalyzed phosphonylation. Optimal conditions for both steps were identified after exploration of various reaction parameters such as solvent, temperature and catalyst. A series of dialkoxyphosphoryl‐substituted A2 B‐porphyrinsZn3 (a –g ) bearing electron‐donating, electron‐withdrawing or sterically bulky substituents at the meso ‐aryl groups were prepared in overall yields close to 40 %. These compounds, being air‐stable and soluble in most organic solvents, are valuable synthetic intermediates because they can be readily transformed into functionalized trans ‐A2 BC‐type porphyrins through regioselective functionalization at the unsubstituted meso position of the macrocycle. Therefore, this approach offers considerable promise for application to the synthesis of trans ‐A2 BC‐type porphyrins, including water‐soluble derivatives, push‐pull chromophores and bis(porphyrin)s. Abstract : A two‐step reaction sequence for the preparation of A2 B‐type porphyrin phosphonate diesters from readily available A2 ‐type porphyrins was developed. These compounds are valuable synthetic intermediates because they can be readily transformed into functionalized A2 BC‐type porphyrin phosphonate diesters through selective functionalization at the unsubstituted meso position.